Gatsby Jay’s self-discipline and sacrifice to humanity: A pointer to achieving the American Dream - AlHasan, Hussein Kanosh (International Journal of Psychosocial Rehabilitation, 2020)
Gatsby Jay is perhaps one of the greatest master-pieces of the 20th century literature. Gatsby Jay, a celebrated American novelist and a ‘Jazz Age’ agent, was considered a well of gentleman with an immense love for the adoring Buchanan Daisy who unfortunately is not only from a different social class but also in some instances unwilling to extend her love to Gatsby.1 Thus, this paper endeavors to bring out the greatness of Gatsby Jay in the context of his career and love perpetuated by self discipline and sacrifice to humanity. It will finally end on how he lost his precious life without achieving his American Dream.